The study of some promising pharmaceutical compositions with urease inhibitory activity for the tuberculosis reactivation prevention - Bomko, T; Martynov, A; Nosalskaya, T (Annals of Mechnikov’s Institute, 2019)
Introduction. The aim of the study was to study the ability to inhibit urease by some pharmaceutical compositions that are promising in the prevention of tuberculosis reactivation . In particular, according to a number references sources, quercetin is able to successfully inhibit urease by a non-competitive mechanism. Another compound - dipyrone (metamizol sodium) according to preliminary molecular modeling has a pharmacophore structure similar to urea. Materials and methods. The biochemical studies (urease activity) of some substances effect on urease was carried out. As the leader substances – inhibitors was used quercetin and metamizole, another substances are not shown inhibition activity on the urease. As the substrate a 0.5% aqueous urea solution was used. The reaction was carried out at a temperature of 37 ° C, the incubation time was 10 minutes. The activity of urease was determined by the color reaction with the hypochlorite reagent. Photometry was performed on a FEK-3M photoelectric colorimeter at a wavelength of 590 nm. Results and discussion. Quercetin and metamizole sodium have the strongest inhibitory properties for urease, since the lowest values of semi-inhibitory concentrations are obtained for them. In the presence of chlorophyllipt, the inhibitory activity of quercetin against urease is not suppressed. Metformin showed no inhibitory activity against urease, and it was low for other substances. Conclusion. The highest anti-urease activity showed a composition based on metamizole sodium and quercetin, a little less - based on quercetin and vitamin D. Also interesting for further research is the composition of quercetin and chlorophyllipt.